Phosphate/hexose 6-phosphate antiport in Streptococcus lactis. - Maloney, P C (1984)
After growth in appropriate media, resting cells of Streptococcus lactis 7962 showed a rapid exchange between external and internal pools of inorganic phosphate. This exchange was not found in other strains of S. lactis (ML3, 133, or K1) or in Streptococcus faecalis. Phosphate exchange in S. lactis 7962 did not require other anions or cations in the assay medium, nor was phosphate influx affected by the membrane potential and pH gradient formed during glycolysis. Thus, the exchange reaction was independent of known ionic drivers (H+, Na+, OH-, etc.). Experiments testing inhibitions of phosphate entry suggested that alternative substrates for exchange included arsenate, as well as the 6-phosphates of glucose, 2-deoxyglucose, fructose, mannose, or glucosamine, and direct studies with 2-deoxyglucose 6-phosphate verified that resting cells could accumulate this sugar phosphate to levels expected for exchange with internal phosphate. Two other observations supported the idea of an exchange between phosphate and sugar phosphate. First, early addition of the heterologous substrate blocked entry of the test compound, whereas later addition caused efflux of preaccumulated material. Second, expression of phosphate exchange and 2-deoxyglucose 6-phosphate transport varied in parallel. Both activities were found at high levels after growth in medium supplemented with rhamnose or arabinose, at intermediate levels with addition of galactose, and at low levels after growth with glucose, fructose, or mannose. We conclude that these findings describe a novel anion antiporter that mediates the exchange of phosphate (arsenate) and sugar 6-phosphates.